Adolescent participation in HIV research: consortium experience in low and middle-income countries and scoping review. Issue 12 (December 2020) - Day, Suzanne; Kapogiannis, Bill G; Shah, Seema K; Wilson, Erin C; Ruel, Theodore D; Conserve, Donaldson F; Strode, Ann; Donenberg, Geri R; Kohler, Pamela; Slack, Catherine; Ezechi, Oliver; Tucker, Joseph D; et al.
Summary: Adolescents in low and middle-income countries (LMICs) have a high prevalence of HIV, therefore, it is important that they are included in HIV research. However, ethical challenges regarding consent can hinder adolescent research participation. We examined examples from the Prevention and Treatment Through a Comprehensive Care Continuum for HIV-affected Adolescents in Resource Constrained Settings (PATC3H) research consortium, which investigates adolescent HIV prevention and treatment in seven LMICs: Brazil, Kenya, Mozambique, Nigeria, South Africa, Uganda, and Zambia. PATC3H researchers were asked to identify ethical and practical challenges of adolescent consent to research participation in these countries. We also did a scoping review of strategies that could improve adolescent participation in LMIC HIV studies. Examples from PATC3H research highlighted many ethical challenges that affect adolescent participation, including inconsistent or absent consent guidance, guidelines that fail to account for the full array of adolescents' lives, and variation in how ethical review committees assess adolescent studies. Our scoping review identified three consent-related strategies to expand adolescent inclusion: waiving parental consent requirements, allowing adolescents to independently consent, and implementing surrogate decision making. Our analyses suggest that these strategies should be further explored and incorporated into ethical and legal research guidance to increase adolescent inclusion in LMIC HIV research.